ACUTE ACALCULOUS CHOLECYSTITIS WITH GALLBLADDER PERFORATION IN CHILDREN - CASE REPOR - Iulia Straticiuc Ciongradi; Laura Trandafir; Doina Mihaila; S.G. Aprodu (Amaltea Medical Publishing House, 2013)
Although relatively common in adult pathology, acute acalculous cholecystitis with gallbladder perforation is a rather infrequent entity in pediatric practice. In many cases, its unspecifi c clinical symptoms and the often inconclusive medical imagining results lead to the diagnosis of acute acalculous cholecystitis being set intraoperatively. Nevertheless, this condition should be considered when setting the differential diagnosis of a peritonitis syndrome in children.